PEMBERDAYAAN KELOMPOK IBU-IBU “LORONG GARDEN” KELURAHAN WALA-WALAYYA KOTAMADYA MAKASSAR - Aminah, .; Hatta, Sitti Rahbiah B. (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The program aims to develop a home organic fertilizer maker business and increase knowledge and skills of housewives who live in alleys of Wala-walayya village, Makassar Municipality, in terms of farming and greening the alleys by utilizing compost and local microorganisms (MOL) made from household waste which is the Leading Innovation Program of the Makassar City Government, also aims to make women able to design and utilize upper part of the drainage channel to store plant pots with beautiful aesthetic value. The target of this activity is increasing knowledge mothers in the alleys Wala-walayya about the concept of greening alleys and laying out alleys properly with organic farming system method, which uses organic fertilizers above the drainage channel around their house that cultivates ornamental plants and other horticultural plants of economic value. At the end of the service, it was found that (1) the knowledge of the target farmers increased about the benefits of fertilization through organic fertilizers, the enthusiasm proved by the residents making their own demonstrated molasses liquid which used as raw material for liquid organic fertilizer; (2) The farmers response are positive and try to make their own liquid organic fertilizers to be tested on their yards, both for ornamental plants and for vegetables and fruits; (3). The enthusiasm of the residents of Wala-walayya village is very high to beautify the alleys where they live by trying to plant horticultural crops on the drainage around the alley so that it looks beautiful like